A comparative appraisal of trademark infringement in Nigeria and United Kingdom (2015)
A trademark performs certain functions such as identifying a seller’s goods and distinguishing them from others, associates the goods with the provider, it serves as a representation of a certain level of quality. A trademark could be a mark, logo, letter, smell, sound, but it is anything that is able to distinguish and identify the goods of a trader from all other traders. The substantive law on trademark is the Trade Marks Act 1965 which regulates trademark in Nigeria today. The Nigerian Trade Marks Act(NTMA) 1965 is based substantially on the old United Kingdom Trade Mark Act (UKTMA) 1938, and replaced with the UKTMA 1994, but the NTMA has remained unreviewed till date. The NTMA excludes other types of infringement such as comparative advertising, dilution and parallel importation, get-up/trade dress, and this is contrary to what obtains in other jurisdictions such as the United Kingdom. Trademark law is an aspect of intellectual property which is in need of urgent reforms in Nigeria but it is nevertheless, deficient in areas as it has not given due recognition to other types of trademark infringement. Nigeria has, over the years, incorporated commerce into the Act but this is still premised on the UKTMA 1938 which does not reflect new trends on trademarks. A problem that could arise is where another person, not being the proprietor of the mark, uses the advertising techniques of the owner of the mark. Thus, when a trademark is being advertised, it could lead to infringement especially where the product is used adversely against the intention of the owner and the result is that it will harm the business of the proprietor irreparably. This paper will examine the ways in which an infringement of trademark can occur and also, other types of infringement which the NTMA has not provided legislative protection